Numerical and Experimental Study of Hydraulic Fracture Active Source Monitoring - Nabipour, Amin; Evans, Brian; Muller, Tobias; Sarmadivaleh, Mohammad (EAGE Publications bv, 2011)
Hydraulic fracturing is one of the most common operations performed on oil and gas wells. As thehydraulic fracture propagation is so complex, monitoring techniques are used to determine the real-timegeometry of the induced fracture. In this work focus is made on numerical and experimental study ofactive monitoring of hydraulic fracture. Discrete element method is used for numerical simulation ofseismic wave transmission in a block of rock being hydraulically fractured. In this method the rock ismodeled by an assembly of round particles. On the other hand the results of an ultrasonic laboratoryexperiment in which a block of cement is fractured, are reported. Numerical and experimental deliversimilar results which are in agreement with those published in literature. The results show interesting information which can be applied for active monitoring of field hydraulic fractures.